2022
DOI: 10.3389/fmed.2022.1011335
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of recent viral pandemics: A literature review

Abstract: Viral pandemics often take the world by storm, urging the medical community to prioritize the most evident systemic manifestations, often causing ocular manifestations to go unnoticed. This literature review highlights the ocular complications of the Monkeypox, SARS-CoV-2, MERS, Ebola, H1N1, and Zika viruses as the most recent viral pandemics. Research into the effects of these pandemics began immediately. Moreover, it also discusses the ocular complications of the vaccines and treatments that were used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…In mpox patients, the pooled prevalence of ophthalmic manifestations has been determined at 9%, globally. Previous analyses based on a smaller number of studies found that the prevalence of ocular lesions ranges from 0.09 to 5% [ 7 , 29 ]. Although this is lower compared to manifestations involving other systems, such as rash, fever, and lymphadenopathy, one in ten patients with mpox could have ophthalmic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mpox patients, the pooled prevalence of ophthalmic manifestations has been determined at 9%, globally. Previous analyses based on a smaller number of studies found that the prevalence of ocular lesions ranges from 0.09 to 5% [ 7 , 29 ]. Although this is lower compared to manifestations involving other systems, such as rash, fever, and lymphadenopathy, one in ten patients with mpox could have ophthalmic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ocular lesions may have a prognostic value in the outcomes of mpox. Corneal ulcerations, in combination with secondary bacterial infections, have been associated with severe ocular complications, including blindness [ 29 ]. Topical trifluridine, when administered together with tecovirimat for mpox patients with varying ophthalmic lesions, has improved the condition without complications [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 vaccination can be complicated by several ocular events such as abducens nerve palsy, acute macular neuro-retinopathy, and multiple evanescent white dot syndrome, vascular events remain the most serious group of complications that needs higher medical attention, due to their high association with vision loss and blindness [6]. Despite their rarity, ocular vascular events were indeed reported following COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Wearing a mask helps reduce the spread of COVID-19 significantly as it covers two parts of the T-zone, namely, the nose and the mouth, while the eye area remains uncovered, which makes the person vulnerable to receiving or transmitting COVID-19. Moreover, different ocular manifestations associated with SARS-CoV-2 in the anterior and posterior segments of the eye were noted ( 3 ). The virus was detected in tears and conjunctival samples, implicating the eye as a potential route for viral entry ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virus was detected in tears and conjunctival samples, implicating the eye as a potential route for viral entry ( 4 , 5 ). Central retinal vein occlusion (CRVO) and central retinal artery occlusion (CRAO) were two of the many vascular manifestations of COVID-19 ( 3 , 4 ). In this review, we assessed the effect of the strict regulations of wearing masks on the practices of different ophthalmic procedures, investigations, and treatments, along with the patient's eye health.…”
Section: Introductionmentioning
confidence: 99%